Manajemen Uang Saku Santri Melalui Santri Identity Card (SIC): Studi di Pondok Pesantren API Asri Tegalrejo Magelang - Minatika, Euis Naely; Purwanto; Pudail (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the impact of using the Santri Identity Card (SIC) on the management of pocket money among students at the API ASRI Tegalrejo Magelang Islamic boarding school. The research method employed is qualitative, with data collected through interviews and observations. Interviews were conducted with 10 students, 5 administrators, and 5 parents of students at API ASRI Islamic Boarding School in Tegalrejo. The data analysis technique utilized is an interactive model analysis. The findings of the study indicate that the use of SIC aids students in various aspects of pocket money management. Firstly, regarding budgeting, SIC allows students to plan their expenditures for various needs such as food, entertainment, savings, and other necessities. Secondly, students can identify spending priorities, helping them distinguish between needs and wants, thereby prioritizing more important expenditures. Thirdly, by recording every expense using SIC, students can track their money usage, which aids in financial control and planning. Lastly, the introduction of financial goals through SIC motivates students to save and plan for specific purchases or vacations. Overall, the use of SIC has proven effective in enhancing students' pocket money management skills, fostering better and more responsible financial habits